GAMBARAN TEKAN INTRAOKULAR PADA PEMAIN MUSIK BIA - Pratasik, Junior; Engka, Nancy; Supit, Siantan (eBiomedik, 2013)
Abstract:Intraocullar Pressure (IOP)closely related to Glaukoma,the 2nd Indonesian blindness causes. Ophtalmology’s riset aproximately during 10 years found an association inflatable music play and increased of IOP. One kind of inflatable music in North Sulawesi which known as Musik Bia (sea shell wind instrument) who had recently recorded in Guiness World Book Of Record as The Biggest Sea Shell Wind Instrument Ensemble. Scientific evidence and fact above have placed inflatable music player especially Bia Music player particularly into high – risk groups of Glaucoma disease This Study aims to reveal the IOP on Bia music player From Batu Villages.Research was done by using cross sectional design. Sample amounted 27 player have fulfilled inclusion criteria that were 11 – 70 years old, physically and mentally healthy, are more than 6 months playing music, be willing to sample and signed the informed consent. The instrument used is the Non – Contack Tonometer. The results of observation shows that The mean IOP in male player is 12.16 mmHg in the right eye and the left eye is worth 12,35 mmHg , whereas the average of IOP in female player is 10.32 mmHg in the right eye and left eye iop mean value is 10.42 mmHg. In 27 bia music player consisting of 23 men and 4 woman had a mean IOP are generallynormal. Keywords: Intraocular Pressure (IOP),Bia Music Player   Abstrak: Tekanan intraokularerat kaitannya dengan penyakit glaukoma yang menjadi penyabab kebutaan kedua di Indonesia. Penelitian dalam dunia Opthalmology kurang lebih 10  tahun terakhir menemukan adanya hubungan bermain musik tiup dan peningkatan tekanan intraokular Salah satu jenis musik tiup di Sulawesi Utara adalah musik bia yang tercatat pada Guiness World Book Of Record sebagai the biggest sea shell music ensemble orchestra.Bukti ilmiah dan fakta diatas menempatkan pemain musik bia kedalam kelompok resiko tinggi penyakit Glaukoma Penelitian ini bertujuan untuk mengetahui gambaran tekanan intraokular pada pemain musik bia di desa Batu.Penelitian ini menggunakan rancangan penelitian cross sectional.Sampel penelitian berjumlah 27 pemain yang telah memenuhi kriteria inklusi yaitu berumur 11-70tahun, sehat jasmani dan rohani, sudah lebih dari 6 bulan memainkan musik, bersedia dijadikan sampel penelitian dan menandatangani informed consent. Alat yang digunakan adalah tonometer non – kontak.Hasil pengamatan menunjukan rerata tekanan intraokular mata kanan pada pemain pria sebesar 12,16 mmHg dan pada mata kiri bernilai 12,35 mmHg, sedangkan pada pemain wanita rerata tekanan intraokular sebesar 10,32 mmHg pada mata kanan dan rerata tekanan intraokular mata kiri bernilai 10,42 mmHg.Pada 27 orang pemain musik bia yang terdiri dari  23 pria dan 4 wanita memiliki rerata tekanan intraokular umumnya normal. Kata Kunci: Tekanan Intraokular,Pemain Musik Bia.